CRAFTS AS A MEANS OF IMPROVING CREATIVITY AND EDUPRENEURSHIP IN EDUCATION OF GRADE 4 AND 5 STUDENTS - Sriyatun; Sitiaeti; Buchori, Achmad (Universitas PGRI Semarang, 2024)
Based on observations made by researchers , Researchers​ find that student student Still Not yet enthusiastic in develop motivation and creativity that they have. For this purpose, teachers are required to raise learning motivation and develop the potential and creativity of students. Answering this challenge, efforts are needed through the development of activities that can channel the potential for creativity and the spirit of eduprenership. Teachers are also expected to be able to develop this potential in learning activities and outside of learning. Researcher give solution on problem the in the form of learning make crafting or craft hand For develop potential and creativity student student as well as grow soul edupreneurship in students grade 4 and 5, okay from process aspect​ make skills and also from aspect How student student develop soul edupreneurship . Creation this crafting practice skills and creativity participant educate For create results interesting work​ as well as can practice motor children . Activities This implemented with use method . Training results show that participant educate capable develop potential creativity and growing soul edupreneurship . In addition , creativity child in process material become results the work that interesting and can marketed in the environment school and also outside environment school . As additional , student skills student For communicate , solve problems and work together in The team also improved.Results observation positive things obtained​​ participant educate is :1. Students begin to recognize the business potential that can be created even from home. or School 2. Participants educate proud with the results of his work and it turns out he can produce income 3. Enthusiasm children​​ For Selling products from their skills at market day events, Qur'an recitation, report card receptions, parenting meetings, 6th grade graduations, and can be deposited at cooperatives School 4. Participants educate more Spirit and creative in follow the lesson art Skills 5. Participants capable cooperate in team Group 6. Able to be creative with Good with materials provided​ and also No in create crafting as learning teaching materials edupreneurship